All Days 2001
DOI: 10.2118/72123-ms
|View full text |Cite
|
Sign up to set email alerts
|

Viscous-Elastic Fluids Can Mobilize Oil Remaining after Water-Flood by Force Parallel to the Oil-Water Interface

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractResidual oil after water flooding appears in three types: oil drops, films and clusters. Work performed using Newtonian fluids shows that to mobilize the residual oil remaining after water flooding, the driving forces, on condition of oil-water IFT (interfacial tension) being constant, need to be increased by one thousand to ten thousand times over that of waterflooding before the capillary forces retaining the residual oil can be overcome [1] . Viscous force… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 2 publications
0
25
0
2
Order By: Relevance
“…It has been shown experimentally that the elasticity of the injected polymer can also contribute to improve the microscopic displacement efficiency (Urbissinova et al, ; Wang et al, , b; Xia et al, ; Xia et al, ; Zhang et al, ). The storage modulus of a material shows its elastic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown experimentally that the elasticity of the injected polymer can also contribute to improve the microscopic displacement efficiency (Urbissinova et al, ; Wang et al, , b; Xia et al, ; Xia et al, ; Zhang et al, ). The storage modulus of a material shows its elastic behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Também tem sido abordado na literatura o fato de que o comportamento viscoelástico do polímero pode melhorar a eficiência de deslocamento da fase oleosa na escala de poros, reduzindo a saturação de óleo residual (Wang et al, 2000(Wang et al, , 2001Lima, 2015 A degradação biológica, apesar de prevalecer sobre os biopolímeros, também pode ocorrer nos polímeros sintéticos. O HPAM pode fornecer nutrição para bactérias redutoras de sulfato.…”
Section: Solução Poliméricaunclassified
“…However, for conditions associated with the Daqing reservoir, researchers (Wang et al 2000, 2001a, 2001b, Xia et al 2004, Wu et al 2007) argued that HPAM solutions reduced S or by 6 to 15 saturation percentage points, even with waterfloods and polymer floods conducted at the same constant capillary number. Notably, Wu et al (2007) observed that HPAM polymers reduced the waterflood S or by up to 15 saturation percentage points (i.e., a S or of 36.8% with waterflooding versus 21.75% for polymer flooding) using a constant capillary number of 5x10 -5…”
Section: Previous Literaturementioning
confidence: 99%